The Department of Medical Sciences of the RAS, Therapeutic Sciences Council meeting: Scientific projects marathon of Russian therapeutic departments "From innovative technologies and education to healthcare practice. Pulmonology: from real clinical practice to promising developments" - O. M. Drapkina; S. N. Avdeev; E. K. Beltyukov; V. V. Naumova; D. V. Kiseleva; A. V. Budnevsky; E. S. Ovsyannikov; S. N. Feigelman; R. E. Tokmachev; E. V. Garbuzova; M. A. Livzan; A. I. Ershova (Кардиоваскулярная терапия и профилактика)
.